A hybrid fuzzy approach of Similarity-Influence-Network and DEMATEL: visualization and analysis - Kamis, Nor Hanimah; Ahmad Shamudin, Nurul Atiqah; Kilicman, Adem; A. Kadir, Norhidayah; Yusoff, Binyamin (Penerbit UTM Press, 2024)
The Social Influence Group Decision Making (SIGDM) entails intricate intra and interpersonal exchanges among a group of experts as they endeavor to persuade others toward reaching a mutually agreed-upon solution. However, prevailing SIGDM approaches often overlook the critical aspect of visualizing criteria interdependencies. This visual representation becomes crucial as it provides supplementary insights into analyzing the significance of criteria and their impacts within decision-making processes. In order to address the oversight of neglecting criteria interdependent relationships, we extend the similarity-influence-network algorithm by integrating a cause-effect visualization procedure inspired by the DEMATEL approach. Additionally, we introduce several supplementary steps to enhance the efficacy of existing methodologies. The proposed model not only fills a gap in the current methodology but also provides accuracy of influence representation by incorporating influence-based collective preferences. This hybrid approach stands as a valuable alternative decision-making tool, providing a comparative analysis of the related existing approaches.